ASUPAN FE, KADAR HEMOGLOBIN, DAN VO2 MAX PADA SISWA SEKOLAH SEPAK BOLA - Evi Puji Rahayu; Mohammad Jaelani (JURNAL RISET GIZI, 2015)
Background: VO2 max is a reference in determining the resistance of one's lung heart. An athlete should have good VO2 max. If an athlete has a low VO2 max, he will quickly experience fatigue so the quality of the sport is not optimal. But the average VO2 max Indonesian soccer athlete is still below the standard.. Objective: The aim of the study was to determine the relationship between Fe intake and hemoglobin level with VO2 max in soccer school students  Methods: is a clinical nutrition study with a cross sectional approach, a total sample of 30 soccer school students. Fe intake was obtained by the semi-quantitative food frequency method. The hemoglobin level was measured by the sianmethemoglobin method and VO2 max was measured by the multistage fitness test method. Relations between variables using the Pearson Product Moment and Rank Spearman correlation test.  Results: 60% of subjects consumed Fe were less, 66.7% had anemia and all subjects had low VO2 max. There is no correlation between Fe intake and VO2 max (p = 0.155). There is a relationship between hemoglobin level and VO2 max (p = 0.021). Conclusion : The higher the hemoglobin level, the higher VO2 max soccer school students.